2019
DOI: 10.1039/c9py01294j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding copolymerisation kinetics for the design of functional copolymers via free radical polymerisation

Abstract: We report the free radical copolymerisation kinetics and co-monomer sequence distribution for a series of functional copolymers based on MMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Owing to the versatility of monomer compatibility and the precise control on the degree of polymerization (DP) of monomers, , the RAFT technology was used to synthesize a series of poly­(MPC)-based precursor polymers named as PMFMa, PMLA, PMF, and PMMa with different ratios of FPMA, MAABO, LAEMA, and AEMA units (Table ). Due to the copolymerization of methacrylates (MPC and FPMA) and methacrylamides (MAABO, LAEMA, and AEMA), which have different reactivities, the obtained copolymers are not completely random. As the backbone unit, the conversion of MPC monomer was controlled around 50% to avoid the side reaction or termination reaction as far as possible.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the versatility of monomer compatibility and the precise control on the degree of polymerization (DP) of monomers, , the RAFT technology was used to synthesize a series of poly­(MPC)-based precursor polymers named as PMFMa, PMLA, PMF, and PMMa with different ratios of FPMA, MAABO, LAEMA, and AEMA units (Table ). Due to the copolymerization of methacrylates (MPC and FPMA) and methacrylamides (MAABO, LAEMA, and AEMA), which have different reactivities, the obtained copolymers are not completely random. As the backbone unit, the conversion of MPC monomer was controlled around 50% to avoid the side reaction or termination reaction as far as possible.…”
Section: Resultsmentioning
confidence: 99%
“…r nBA (r 2 )~1 indicated similar reactivity of nBA and CyA to the propagating nBA radical chain ends, while r CyA (r 1 ) < 1 suggested that nBA has a preference towards adding to the CyA terminated propagating radical chain ends. The lower self-propagation compared to cross-propagation of CyA monomers was presumably attributed to its bulkier cytosine pendant unit, which inhibited the addition of another CyA monomer to a CyAterminated radical [33]. Although the calculated reactivity ratios demonstrated that nBA propagates favorably at low conversions and thereby generating nBA-enriched polymer chains, it is of great interest to probe if the polymer displays a composition gradient along the polymer chain due to concentration effects at higher monomer conversions.…”
Section: Synthesis Of Cya and Ucya Triblock Copolymermentioning
confidence: 98%
“…This is explained by the fact that PEO 5 MEMA is even more preferable for cross-polymerization than MMA. This assumption may be justified by recent studies of Boulding et al [41], where authors stated that the reactivity ratio of MMA is higher if compared to the used PEG-methacrylate during the free radical polymerization of such monomers.…”
Section: Synthesis Of P(st-co-peo 5 Mema) Copolymersmentioning
confidence: 99%